IMPACT OF REGIONAL REVENUE AND ALLOCATION FUNDS ON FINANCIAL INDEPENDENCE AND ECONOMIC GROWTH IN RIAU ISLANDS 2013-2023 - Sri Wahyu Handayani (International Journal Management and Economic, 2025)
This research aims to analyze the influence of Regional Original Income (PAD) and General Allocation Funds (DAU) on regional financial independence and economic growth in the Riau Islands Province in 2013-2023. The research method used is a quantitative method with secondary data in the form of budget realization reports. Data analysis was carried out using multiple linear regression and path analysis to test the direct and indirect effects between variables. The research results show that PAD has a positive and significant influence on regional financial independence, while DAU has no significant influence. Apart from that, neither PAD nor DAU have a significant effect on regional economic growth. This research identifies limitations in the sample coverage which only involves districts/cities in the Riau Islands Province as well as low Adjusted R Square values, which indicate the existence of other variables that have not been studied but have the potential to influence the results. This research recommends further studies to expand the regional coverage, extending the period research time, as well as adding other relevant variables to enrich the analysis. It is hoped that these findings will provide insight for local governments in increasing financial independence and economic growth through optimizing regional resources.